GOLD NANOPARTICLES FROM BROWN ALGAE OF TURBINARIA SPECIES AND THEIR ANTI- INFLAMMATORY ACTIVITY - Priyam Bharathidasan, Dr. Abirami Arthanari (Chelonian Research Foundation, 2023)
Introduction Inflammation is a complex biological response that plays a crucial role in the body's defense mechanism. However, dysregulated inflammation can contribute to the development of various chronic diseases, such as cardiovascular diseases, cancer, and autoimmune disorders. Brown algae are common marine creatures along the shore that are recognised for having a wealth of bioactive chemicals. Due to their numerous pharmacological characteristics, which include anti-inflammatory actions. Aim To study the Gold nanoparticles from brown algae of Turbinaria sp. and their anti-inflammatory potential Materials and methods Preparation of crude extract from Turbinaria species, synthesis of gold nanoparticles from aqueous extract of seaweed, protein denaturation assay was conducted to evaluate the anti- inflammatory activity Results Protein denaturation assay was done on the gold nanoparticles from brown algae. It was found that the gold nanoparticles when compared to the standard diclofenac showed high anti- inflammatory activity. It was observed that the anti- inflammatory activity of the extract increased as the concentration increased. Discussion The results indicated that the marked attenuation of protein denaturation in a concentration dependent manner with maximum action of 47% at 100μg/ml. total flavonoid contents and the aqueous fraction of Turbinaria sp. exhibited marked attenuation of thermal-induced protein denaturation. Of the tested species, total flavonoid contents of the species were most dominant in the inhibition of protein denaturation. Conclusion In conclusion, the synthesis of AuNPs from brown algae of Turbinaria sp. demonstrates their anti- inflammatory potential. These nanoparticles hold promise for the development of novel therapeutic strategies for inflammation-related disorders. Keywords: Brown algae, Inflammation, Protein denaturation assay, Gold nanoparticles, Diclofenac